Persica qeshmensis gen. nov. sp. nov from the Persian Gulf (Platyhelminthes: Polycladida: Acotylea), with remarks on reproductive structures - Maghsoudlou, Abdolvahab (2015)
A new genus of acotylean polyclad, Persica qeshmensis gen. nov. sp. nov. (Acotylea, Pleioplanidae), was collected from intertidal rocky shores of the Northern Persian Gulf, Iran. The genus Persica is established on the presence of small tentacles; tentacular and cerebral eyes; spermiducal bulbs; true seminal vesicle; prostatic vesicle of atomata-type; muscular coiled ejaculatory duct, provided with a stylet, absence of a vagina bulbosa or Lang's vesicle. Persica qeshmensis is characterised by a sandy beige to light brown background colour, with pale brown microdots, light grey ventral body surface, coiled ejaculatory duct embedded in parenchymatous cell mass, elongated sigmoid stylet, a well-developed penis sheath located in a small male atrium, and with a non-muscular blind chamber extending anteriad from the vagina to the level of the genital sucker.